Microwave Discharge Electrodeless Lamps. Part VIII: Continuous On‐Site Solar Energy Remediation of Contaminated Water. Issue 1 (29th September 2015) - Horikoshi, Satoshi; Nishimura, Tomoki; Tsutsumi, Hideya; Serpone, Nick
Abstract: Microwave discharge electrodeless lamps (MDELs) have been examined for continuous on‐site field treatment of contaminated water using solar cells to provide the necessary electrical power. The equipment aimed to decontaminate water in areas impacted by natural disasters such as the extensive earthquake that hit Eastern Japan in 2011. An energy‐saving semiconductor microwave generator provided the microwaves to activate the MDELs in a microwave/UV reactor setup operated using a single‐mode applicator and an E / H tuner. The herbicide 2, 4‐dichlorophenoxyacetic acid degraded within a shorter time compared to methylene blue at a defined flow rate through the microwave/UV reactor. Sterilization of natural water contaminated with the bacterial microorganism Escherichia coli was complete within 20 min. Abstract : Microwave discharge electrodeless lamps activated by microwaves from a semiconductor generator were used on‐site to treat contaminated water with solar cells providing the electrical power. Such a system is able to degrade relatively high concentrations of organic pollutants and sterilize water contaminated with bacteria on‐site in relatively short time.